Fast genetic mapping of complex traits in C. elegans using millions of individuals in bulk - Alejandro Burga (Nature Portfolio, 2019)
QTL mapping in multicellular animals usually requires generation, maintenance, and phenotyping large panels of recombinant individuals. Here, the authors develop ceX-QTL mapping, a method for fast genetic mapping via bulk selection on millions of unique recombinant C. elegans individuals.